The Effect of Coupling Agent on Thermal Properties and Morphology of Paper Sludge Filled Polypropylene (PP)/Ethylene Propylene Diene Terpolymer (EPDM) Composites - Salmah Husseinsyah, Dr. Ir.; Che Mohd Ruzaidi, Ghazali, Assoc. Prof.; Supri, A. Ghani, Dr. (Universiti Malaysia Perlis (UniMAP), 2008)
Organized by Universiti Malaysia Perlis (UniMAP), 9th - 12th June 2007 at Park Royal Hotel, Penang.